Ropeginterferon-alfa2b resolves angina pectoris and reduces JAK2V617F in a patient with clonal hematopoiesis of indeterminate potential: A case report - Egyed, Miklos; Kajtar, Bela; Foldesi, Csaba; Skov, Vibe; Kjær, Lasse; Hasselbalch, Hans Carl (Frontiers in Hematology, 2022)
Abstract . The JAK2V617F mutation is an acquired somatic mutation, which is prevalent in patients with the Philadelphia-chromosome negative myeloproliferative neoplasms (MPNs). In these diseases the mutation gives rise to constitutive JAK-STAT signaling with increased blood cell counts and in vivo activation of neutrophils and platelets as well, which altogether contribute to a chronic inflammatory and thrombogenic state with a 12-fold increased risk of coronary disease. Treatment with recombinant interferon-alpha2 (rIFN) reduces the JAK2V617F allelic burden in a large number of MPN-patients -.Long-term treatment with rIFN associates with low-burden JAK2V617F in a subset of patients and a decreased thrombosis risk as well. In the general population the JAK2V617F mutation has been shown to associate with ischemic heart disease and thrombosis . Based upon the above observations we herein report the first patient with CHIP-JAK2V617F , in whom treatment with rIFN resolved severe angina pectoris. During a short period off rIFN the symptoms reappeared to resolve in concert with reduction of JAK2V617F allele burden, when rIFN was reinstituted.. The JAK2V617F mutation may be a novel therapeutic target to prohibit the development of cardiovascular diseases using rIFN either as monotherapy or in combination with potent anti-inflammatory agents.